Reinterpretasi Teori Language Game dalam Bahasa Dakwah Perspektif Ludwig Wittgenstein - Umi Wasilatul Firdausiyah; Khairul Fikri (Universitas Nahdlatul Ulama Surabaya, 2021)
The discourse of this study focuses on the language game theory by Ludwig Wittgenstein which is applied in the da’wah language. The purpose of the study is to determine the significance of the language game theory applied to the da’wah language. The research method used is library research, with data analytics in the form of descriptive-interpretative, and is assisted by Hans George Gadamer’s effective hermeneutic theory in studying language game theory and Wittgenstein’s idea. The results of this study are sufficient to answer the significance of the language game theory applied to the da’wah language, with two points. First, language game theory can be applied in da’wah language. Second, the use of language game theory can attract the interest of da’wah listeners. These two points have implications for the actions or behavior of the da’wah listeners, which is called compulsive and impulsive behavior. cThus it can be understood that language and da’wah are an inseparable bond